Analisis Usability Sistem Informasi Akademik UNTAG Menggunakan Metode User Experience Questionnaire - Zulmi, Muhammad Nizar; Safitri, Eristya Maya; Rahmawati, Rafika (STMIK Banjarbaru, 2025)
The advancement of information technology has facilitated higher education institutions in conducting educational processes more effectively, efficiently, and transparently. One such implementation is the SIAMIK “UNTAG” application, developed by Universitas 17 Agustus 1945 Surabaya to support students' academic progress. However, its implementation still faces challenges, such as difficulty navigating menus and operating the application, which affects students’ academic activities.This study aims to evaluate the user experience of the SIAMIK “UNTAG” application using the User Experience Questionnaire (UEQ), which includes six aspects: attractiveness, clarity, efficiency, accuracy, stimulation, and novelty. Data were collected from 388 respondents using simple random sampling and analyzed with the UEQ Data Analysis Tool. The results indicate a generally positive user experience; however, improvements are needed in innovation, clarity, and user motivation. The average scores were: attractiveness (1.60), clarity (1.35), efficiency (1.42), accuracy (1.43), stimulation (1.42), and novelty (1.43).Keywords: SIAMIK UNTAG; Usability analysis; User Experience Questionnaire AbstrakPerkembangan teknologi informasi telah mempermudah perguruan tinggi dalam menjalankan proses pendidikan secara efektif, efisien, dan transparan. Salah satu implementasinya adalah aplikasi SIAMIK “UNTAG” yang dikembangkan oleh Universitas 17 Agustus 1945 Surabaya guna mendukung kelancaran studi mahasiswa. Namun, dalam implementasinya masih terdapat kendala seperti kesulitan dalam navigasi menu dan pengoperasian aplikasi, yang berdampak pada proses akademik mahasiswa. Penelitian ini bertujuan mengevaluasi pengalaman pengguna aplikasi SIAMIK “UNTAG” menggunakan metode User Experience Questionnaire (UEQ) yang mencakup enam aspek: daya tarik, kejelasan, efisiensi, ketepatan, stimulasi, dan kebaruan. Data diperoleh dari 388 responden melalui teknik simple random sampling dan dianalisis menggunakan UEQ Data Analysis Tool. Hasil menunjukkan pengalaman pengguna tergolong positif, namun diperlukan peningkatan pada aspek inovasi, kejelasan, dan motivasi. Nilai rata-rata aspek: daya tarik (1,60), kejelasan (1,35), efisiensi (1,42), ketepatan (1,43), stimulasi (1,42), dan kebaruan (1,43).